Effect of Preseating on the Extrusion of Excess Cement at the Crown- Abutment Margin and the Associated Tensile Force for Cement-Retained Implant Restorations. A Pilot Study - Jiménez Corrales DDS, Rodrigo (2015)
The purpose of this study was to compare the effect of preseating prior to cementation on the amount of cement excess at the crown-abutment margin and to analyze the associated tensile force after cementation. Preseating of the crown on an abutment analog was evaluated. Ten implant copings were cemented with temporary cement on ten straight implant abutments. The amount of cement excess at the crown margins was measured by weight. Axial tensile force was measured 24 hours after the cementation. Results were statistically analyzed using ANOVA (p= 0.05). Preseating of the crown had a significant effect on the amount of cement excess at the crown margin (p<0.05), without lowering the tensile strength values significantly. When cementing crowns on implant abutments with temporary cement a preseating protocol might be advisable in order to reduce the amount of cement excess at the crown margin.